Circulating tumor HPV DNA as an alternative method to determine HPV status in oropharyngeal squamous cell carcinoma. (May 2023) - Lambert, Todd; Tasoulas, Jason; Flores, Melissa; Sheth, Siddharth; Patel, Samip N.
Highlights: ctHPVDNA can effectively confirm HPV-status. ctHPVDNA may replace additional biopsies in patients with indeterminate FNA results. A wider application of ctHPVDNA may allow for improved diagnostics. Abstract: Human Papilloma Virus (HPV) testing is mandatory for all newly diagnosed oropharyngeal squamous cell carcinoma (OPSCC) due to its importance for prognostication and aiding in treatment decision making. Fine needle aspiration (FNA) is a widely used and accepted diagnostic tool for OPSCC. Although FNA can accurately determine histological diagnosis, results are often indeterminate or lack insufficient samples for HPV testing. For samples with an indeterminant FNA, we propose an alternate method for determining HPV status using circulating tumor tissue modified HPV DNA (ctHPVDNA). We report three cases that confirmed HPV status using ctHPVDNA following an indeterminate FNA. If validated, this non-invasive assay could prevent the need for repeat FNAs or operative biopsies for the sole purpose of determining HPV status.